Sharing spaces : essays in honour of Sherry Olson - Sweeny, Robert (Mercury series. History ;, 2020)
"Sherry Olson has almost always worked with others, inspiring them to ground their research in an empathetic understanding of the human condition. Through this team work, she has made signal contributions in fields as diverse as environmental, social, urban, and women's histories, as well as public health, demography, and geographic information systems (GIS). In this volume, a critical assessment of her life's work is complemented by original pieces advancing our knowledge in these remarkably diverse fields. From the environmental impact of colonial settlement in New Zealand to racial segregation in Chicago, from the demography of the Mauricie and marriage patterns of Quebec City to the inns, gay spaces, and landladies of Montreal, this collection demonstrates the complexity of sharing space in the past and its centrality to any critical understandings of the global challenges we face in the present."--